Immune checkpoint inhibitors rechallenge in urological tumors: An extensive review of the literature. (February 2022) - Bimbatti, Davide; Maruzzo, Marco; Pierantoni, Francesco; Diminutto, Alberto; Dionese, Michele; Deppieri, Filippo M.; Lai, Eleonora; Zagonel, Vittorina; Basso, Umberto
Graphical abstract: Highlights: Different immune checkpoint inhibitors are approved for urological tumors. Little is known about the treatment after progression or toxicity on immunotherapy. Retreatment with an immune checkpoint inhibitor could be feasible in some cases. Abstract: Immune checkpoint inhibitors (ICIs) have led to a significant change in the treatment of urological tumors where several agents are currently approved. Yet, most patients discontinue treatment due to disease progression or after the onset of severe immune-related adverse events (IRAEs). Following promising results in melanoma patients, retreatment with an ICI is receiving increasing attention as an attractive option for selected patients. We performed a literature review focusing on the feasibility, safety, timing and activity of ICI rechallenge in genitourinary cancers where very little information is available. We classified the different ICI retreatment strategies into three main clinical scenarios: retreatment after terminating a prior course of ICI while still on response; retreatment after interruption due to IRAEs; retreatment after progression while on ICI therapy. The pros and cons of these options in the field of urological tumors are then discussed, and critical suggestions proffered for the design of future clinical trials.